AD, Volume 30, n° 3, 2005 - Full Issue - journal system (Africa Development, 2022)
Contents 1. All knowledge is first of all local knowledge: An introduction Theophilus I. Okere, Chukwudi Anthony Njoku & René Devisch .............................1 2. Is there one science, Western science? Theophilus Okere ............................20 African Mathematical Systems 3. Traditional Igbo numbering system Patrick Mathias C. Ogomaka .........................35 4. Ethnomathematics, geometry and educational experience in Africa Paulus Gerdes ....................................48 African Health Systems 5. Domesticationof medicinal plants in Southestern Nigeria A. E. Ibe and Martin I. Nwufo ...........................66 6. Understanding Igbo medicine practitioners Patrick Iroegbu ......................................78 7. Cultural modes of comprehending and healing insanity: The Yaka of DR Congo René Devisch .............................93 African Arts 8. Subjectivity in servitude: The servant and indigenous family arrangements in written Igbo drama Frances N. Chukwukere ............................112 9. I dance Ala Igbo (Poem) Chikwendu P. K. Anyanwu ..........................130 Review Article/Revues de livres Spectralizing Bergson and the Dilemmas of Decolonization. A review of Messay Kebede, Africa's Quest for a Philosophy of Decolonization, 2004. Sanya Osha .................................13